Factors that Cause the Occurrence of Siri Marriage in Tualang District - Paisal Ahmad Dalimunthe (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose – In the procedural rules of marriage within the Indonesian Islamic society, it is stipulated that marriages must be officially recorded and published in accordance with Marriage Law No. 1 of 1974. In reality, not all segments of the Indonesian population adhere to the established procedures or rules. This is evidenced by the fact that a portion of the population in the Tualang District of Siak Regency still engages in unregistered marriages that are not officially documented or published, which deviates from the provisions of Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law. This study aimed to identify the factors underlying the occurrence of unregistered marriages in the Tualang District. Methods – To achieve this objective, the researcher employed qualitative research methodology. Data collection was carried out using observation, interview, and documentation methods. The data validity testing technique used was triangulation of sources and methods. Data analysis was conducted using an interactive analysis model consisting of data collection, data reduction, data presentation, and drawing conclusions. Findings – The research findings indicate that the practice of unregistered marriages in the Tualang District is similar to regular marriages, with the key distinction being the lack of official documentation. The factors contributing to unregistered marriages in the Tualang District include: out-of-wedlock pregnancies, economic factors, and the desire for polygamy. Research implications/limitations – The impacts of unregistered marriages on the community include ease of conducting marriages, difficulties in obtaining birth certificates for children, a higher likelihood of divorce, document forgery, and conflicts. Originality/value – The results of this research are expected to be a practical reference for the community and government to overcome the problem of nikah siri. The factors that cause nikah siri described in this research can be an illustration for the government to be able to formulate policies related to the problem of siri marriage.